Pengaruh Peranan Komitmen Organisasi dan Employee Engagement Terhadap Kinerja Pegawai pada Kantor Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Sikka - Maria Meiling Fanggi Dae; Imanuel Wellem; Kristiana Reinildis Aek (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2025)
This study is motivated by issues related to employee performance at the Public Works and Spatial Planning Office of Sikka Regency. The objectives of this study were: (1) to describe employee performance, the role of organizational commitment, and employee engagement, (2) to analyze the influence of organizational commitment and employee engagement on omployee performance both partialy and simultaneously at the Public Works and Spatial Planning Office of Sikka Regency. The sample used in this study consisted of 75 respondents, selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, specifically multiple linear regression. Descriptive analysis results indicated that the variables of employee performance, organizational commitment, and employee engagement were categorized as very good. The t-test results showed that, partially, organizational commitment and employee engagement had a positive and significant effect on employee performance. The F-test results indicated that, simultaneously, organizational commitment and employee engagement significantly influenced employee performance. The coefficient of determination in this study was 63.3%.